Sustainable Process Engineering - Szekely, Gyorgy (De Gruyter Textbook Ser., 2021)
Sustainable process engineering is a methodology to design new and redesign existing processes that follow the principles of green chemistry and green engineering, and ultimately contribute to a sustainable development. The newest achievements of chemical engineering, opened new opportunities to design more efficient, safe, compact and environmentally benign chemical processes. The book provides a guide to sustainable process design applicable in various industrial fields. • Discusses the topic from a wide angle: chemistry, materials, processes, and equipment. • Includes state-of-the-art research achievements that are yet to be industrially implemented. • Transfers knowledge between chemists and chemical engineers. • QR codes direct the readers to animations, short videos, magazines, and blogs on specific topics • Worked examples deepen the understanding of the sustainable assessment of chemical manufacturing processes.